Refugees of the revolution : experiences of Palestinian exile - Allan, Diana (Diana Keown) (Stanford studies in Middle Eastern and Islamic societies and cultures., 2014)
Some sixty-five years after 750,000 Palestinians fled or were expelled from their homeland, the popular conception of Palestinian refugees still emphasizes their fierce commitment to exercising their ""right of return."" Exile has come to seem a kind of historical amber, preserving refugees in a way of life that ended abruptly with ""the catastrophe"" of 1948 and their camps-inhabited now for four generations-as mere zones of waiting. While reducing refugees to symbols of steadfast single-mindedness has been politically expedient to both sides of the Arab-Israeli conflict it comes at a tr